La mobilità degli studenti universitari Sardi Un'analisi comparativa della domanda e dell'offerta di istruzione universitaria in Sardegna - Sulis, Isabella; Columbu, Silvia; Carta, Aurelio; Aru, Pierluigi (RESOCONTI, 2023)
This volume contains the main findings from the two-year project "Students' mobility in Sardinia. A comparative analysis of the tertiary education supply in Sardinia." The study of Sardinian student mobility is part of a more general line of research on student mobility that has involved researchers from several Italian universities since 2014.